Ber-English Ria English Speaking Community: Politeness Used - Annisa Nurul Shabrina; Sukma Nur Ardini (Universitas Dian Nuswantoro, 2019)
As the fast development of technology in this globalization era, people become more attracted to social media. In using social media itself, we still need politeness just like the oral communication. This study aimed at analyzing the politeness strategies used in Ber-english Ria ‘Line’ group chat. The study described the politeness strategies used in Ber-english Ria line grup chat and the application among those strategies. The study was analyzed descriptively based on related politeness strategies classification of Brown and Levinson citied in Athenia Barouni (2013). The data were analyzed and grouped into the classification. The result showed that the group chat members mostly used positive politeness followed by negative politeness, off record strategy, and the least used is bald on record strategy. It showed that the group chat members’ politeness was in the middle of very polite and straightforward. In the end, the most applicable politeness strategy used in Ber-english Ria ‘Line’ group chat was positive politeness strategy. The result of this study showed how important the politeness even in written communication. It can be used in using social media to lessen the misunderstanding.